(untitled) (Docentes 2.0 Journal, 2020)
Education has a fundamental role in the development of society, being one of the engines of its evolution and progress. In the last decades, information and communication technologies have brought about great changes in the way individuals communicate and interact, generating real breaks in the ways of learning, teaching, discovering, constructing and reproducing knowledge, a situation that has led to ask questions about the relevance of educational systems. Within this framework, universities are going through a period of metamorphosis, in order to achieve relevance to the environment, in this difficult task, processes such as virtualization and internationalization open up new opportunities and expand their possibilities for development. Virtualization goes hand in hand with internationalization, since virtual education is an essential tool to offer programs in a global context, opening the way for alliances, academic mobility, internationalization of the curriculum, participation in collaborative networks; actions that promote positioning and competitiveness. The Yacambú University, always at the forefront, has decided to offer answers to this reality by working to consolidate a leading institution, capable of supporting social transformation in the search for sustainable development.